Does Global Citizenship Require Modern Technology? - Nigel Dower (Ideas y Valores)
A double answer is given to the question: 'does global citizenship require modern technology?' First, it does not because the idea of global citizenship as membership of a universal moral commnunity goes back to the ancient Stoics. Second, it does, because the adequate expression of globalresponsibility in the modern world requires the development of global culture and global institutions for which modern technologies of communication and transportation are crucial: modern technology furthemore gives us both knowledge of the world and the capacity to act at a distance. The discussion provides a peg on which to defend the idea of global citizenship in both its ethical and its institutional aspects against the criticisms made of it for instance from relativist or communitarian perspectives.